UPAYA GURU PAI DALAM MENINGKATKAN LITERASI MEMBACA SISWA KELAS IV MELALUI MEDIA SUDUT BACA DI SDN GROBOGAN 2 MOJOWARNO JOMBANG - Fatikah, Noor; Sofi Ainiyah, Dewi (ILJ: Islamic Learning Journal, 2024)
The teacher's efforts in increasing reading literacy, some teachers havea different or inadequate understanding of reading literacy, the teacher should be agood role model for their students. In this modern era, we find many problemswhere students are less interested in studying religious knowledge, especiallyregarding Islamic Religion Subjects and tend to prioritize subjects that are generalin nature rather than religious, so that students neglect learning from IslamicStudies. The purpose of this research is to describe: 1. To describe reading literacyin students of SDN Grobogaan 2 Mojowarno Jombang. 2. To escribe the efforts ofPAI teachers in increasing reading literacy of fourth grade students at SDNGrobogan 2 Mojowarno Jombang. This type of research uses qualitative researchand uses a qualitative descriptive research design using interview, observation anddocumentation methods. The analysis technique in this study uses DataReduction, Data Display and Verification. The conclusion of this research. (1)reading literacy in grade IV students at SDN Grobogan 2 Mojowarno Jombang. a.Lack of interest in reading literacy b. Lack of concentration in readingcomprehension. c. Students who do not like to read. (2) PAI teachers' efforts toimprove students' reading literacy through the media of reading corners. a.Decorate the reading corner neatly and beautifully. b. Giving Gifts. c. Providemotivation or ice breaking before and after reading literacy. d. Encourage childrento tell about what they have read e. Read in the reading corner for 15 minutes. f.Provides various types of books.